2014
DOI: 10.1371/journal.pone.0086460
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Association between Serotonergic Gene Polymorphisms and Obstructive Sleep Apnea Syndrome

Abstract: Background5-Hydroxytryptamine receptor (5-HTR) and 5-hydroxytryptamine transporter (5-HTT) gene polymorphisms have been reported to be associated with susceptibility to obstructive sleep apnea syndrome (OSAS). The associations, derived from sporadic, inconsistent, small-sample-size studies, need to be evaluated further in a meta-analysis.MethodsRelevant studies were identified by searching PubMed, Embase, The Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu. Eligible data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
0
20
0
3
Order By: Relevance
“…We also examined generalizability of previously reported AHI candidate gene results to our Hispanic/Latino cohorts (see Table E6) (23)(24)(25)(26)(27)(28)(29)(30)(31). Of 17 SNPs tested We searched for SNPs with supporting ENCODE or Roadmap Epigenomics regulatory evidence as calculated by HaploReg (33).…”
Section: Association Signal Generalizability Into Other Populationsmentioning
confidence: 99%
“…We also examined generalizability of previously reported AHI candidate gene results to our Hispanic/Latino cohorts (see Table E6) (23)(24)(25)(26)(27)(28)(29)(30)(31). Of 17 SNPs tested We searched for SNPs with supporting ENCODE or Roadmap Epigenomics regulatory evidence as calculated by HaploReg (33).…”
Section: Association Signal Generalizability Into Other Populationsmentioning
confidence: 99%
“…In this process, 5-HT reuptake is mediated by the 5-HT transporter (5-HTT). VNTR can affect enhancer function and transcription of the 5-HTT gene, and LPR can influence 5-HT [38][39][40], which may contribute to the susceptibility of OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism of the genes that code for 5-HTR alter its transcription, affecting the number of receptors in the serotoninergic system, and may increase the risk of OSAHS. Recently, 3 meta-analyses (6)(7)(8) revealed that no differences were observed in the prevalence of T102C (rs6311) polymorphisms in the case and control groups (P>0.05). However, the -1438G-A polymorphism in the 5-HTR2A gene was significantly correlated with the increased risk of OSAHS, showing that the 'T' and 'C' allele are not involved in OSAHS.…”
Section: Introductionmentioning
confidence: 99%